2019
DOI: 10.1108/etpc-09-2018-0081
|View full text |Cite
|
Sign up to set email alerts
|

Accommodating linguistic prejudice? Examining English teachers’ language ideologies

Abstract: Purpose The purpose of this study is to support the integration of scientifically grounded linguistic knowledge into language teaching in English Language Arts (ELA) classrooms through building an understanding of what teachers currently know and believe about language. Design/methodology/approach In total, 310 high school English teachers in the USA responded to a survey about their language beliefs. Statistical analysis of responses identified four distinct constructs within their belief systems. Sub-scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…For example, Razfar, Rumenapp, and Torres (2020) conducted focus groups with 15 administrators at majority-Black schools and found that, while many believed AAVE could be used as an educational resource for connecting with Black students, they also tended to believe AAVE "was a lesser variety of English and had no currency in mainstream U.S. society" (p. 16). Administrator beliefs about linguistic diversity are significant because research suggests they influence teachers' own beliefs and classroom practices (Blake & Cutler, 2003), and the longer a teacher works within a school culture that marginalizes AAVE, the more strongly that teacher will internalize a negative view of AAVE (Metz, 2019). Indeed, two massive surveys of teachers in Ohio (Diehm & Hendricks, 2021) and Missouri (Metz, 2019) found that even though most teachers reject the assumption that AAVE is inherently inferior to other varieties of English, they do not think it appropriate for classroom instruction.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Razfar, Rumenapp, and Torres (2020) conducted focus groups with 15 administrators at majority-Black schools and found that, while many believed AAVE could be used as an educational resource for connecting with Black students, they also tended to believe AAVE "was a lesser variety of English and had no currency in mainstream U.S. society" (p. 16). Administrator beliefs about linguistic diversity are significant because research suggests they influence teachers' own beliefs and classroom practices (Blake & Cutler, 2003), and the longer a teacher works within a school culture that marginalizes AAVE, the more strongly that teacher will internalize a negative view of AAVE (Metz, 2019). Indeed, two massive surveys of teachers in Ohio (Diehm & Hendricks, 2021) and Missouri (Metz, 2019) found that even though most teachers reject the assumption that AAVE is inherently inferior to other varieties of English, they do not think it appropriate for classroom instruction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Administrator beliefs about linguistic diversity are significant because research suggests they influence teachers' own beliefs and classroom practices (Blake & Cutler, 2003), and the longer a teacher works within a school culture that marginalizes AAVE, the more strongly that teacher will internalize a negative view of AAVE (Metz, 2019). Indeed, two massive surveys of teachers in Ohio (Diehm & Hendricks, 2021) and Missouri (Metz, 2019) found that even though most teachers reject the assumption that AAVE is inherently inferior to other varieties of English, they do not think it appropriate for classroom instruction. The tension between teachers' beliefs in the legitimacy of AAVE and their failure to honor it in their teaching has been explored in several case studies (Godley, Carpenter, & Werner, 2007;Metz, 2018;Orzulak, 2015;Wheeler, 2010;Woodard & Rao, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This ideology is prevalent across the broader American society (e.g., Arredondo, 2012;Baldwin, 1979;Greco, 2021;Martin et al, 2010;Sanchez, 1998) as well as in schools. In his survey of over 300 teachers in Missouri, for example, Metz (2019) found teachers held critical views of language; in other words, they "disagree with statements that associate language use with particular levels of intelligence, kindness or morality" (p. 25). At the same time, they see the larger US society as being suffused with linguistic prejudice, and thus, they "tend to support the idea that [standardised English] is correct, and that students should use [standardised English] rather than other dialects of English" (Metz, 2019, p. 25).…”
Section: Language Ideologies In the United Statesmentioning
confidence: 99%
“…Martinez, 2017;R. Martínez, 2010;Metz, 2018Metz, , 2019. Educators, and many others across society, maintain beliefs about SL even without being able to specifically define the contours of that language (Flores & Rosa, 2015;Lippi-Green, 2012;Smakman, 2012).…”
Section: Education Research and Language Practicesmentioning
confidence: 99%
“…Given the increased attention to racial justice more broadly and antiracist education specifically, ELA teacher educators must be aware of the status and treatment of AAVE in K-12 institutions and perhaps reconsider the advice we give preservice and in-service teachers about how best to capitalize on AAVE proficiency. In this study, we contribute to recent research (Diehm & Hendricks, 2021;Metz, 2018Metz, , 2019Razfar, Rumenapp, & Torres, 2020;Wheeler, 2016;Woodard & Rao, 2020) that documents how AAVE is perceived and treated in classroom settings. We extend this work by drawing on a new data source: interviews with experienced Black educators who are themselves fluent in AAVE, have capitalized on this fluency in instructional settings, and who have seen up close how perceptions of AAVE among students, teachers, administrators, and community members affect literacy education for students whose primary dialect is AAVE.…”
Section: Introductionmentioning
confidence: 99%